2021
DOI: 10.3102/0034654321990713
|View full text |Cite
|
Sign up to set email alerts
|

Video Improves Learning in Higher Education: A Systematic Review

Abstract: Universities around the world are incorporating online learning, often relying on videos (asynchronous multimedia). We systematically reviewed the effects of video on learning in higher education. We searched five databases using 27 keywords to find randomized trials that measured the learning effects of video among college students. We conducted full-text screening, data extraction, and risk of bias in duplicate. We calculated pooled effect sizes using multilevel random-effects meta-analysis. Searches retriev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(99 citation statements)
references
References 94 publications
4
85
0
10
Order By: Relevance
“…Hence, in newer studies where learners have this type of control in the instructional video condition, no difference in comprehension outcome has been found between video and reading (e.g., Burin et al, 2021;List, 2018;Merkt et al, 2011;Salmerón et al, 2020;Tarchi et al, 2021). In their recent review, Noetel et al (2021) found that combining viewer-controlled videos with traditional teaching resulted in strong improvements in students' learning.…”
Section: Students' Comprehension Of Educational Streaming Videosmentioning
confidence: 99%
“…Hence, in newer studies where learners have this type of control in the instructional video condition, no difference in comprehension outcome has been found between video and reading (e.g., Burin et al, 2021;List, 2018;Merkt et al, 2011;Salmerón et al, 2020;Tarchi et al, 2021). In their recent review, Noetel et al (2021) found that combining viewer-controlled videos with traditional teaching resulted in strong improvements in students' learning.…”
Section: Students' Comprehension Of Educational Streaming Videosmentioning
confidence: 99%
“…Questionably, of the numerous literature reviews on the use of video in TE over the last 10 years (i.e., Brouwer, 2011;Rook and McDonald, 2012;Tripp and Rich, 2012;Marsh and Mitchell, 2014;Gaudin and Chaliès, 2015;Christ et al, 2017;Major and Watson, 2018;Cattaneo et al, 2019;Hamel and Viau-Guay, 2019), none of them reported any use of 360 °video. Further, in higher education, Noetel et al (2021) reported the potentialities and benefits of video, but they didn't identify 360 °video uses.…”
Section: Introductionmentioning
confidence: 99%
“…The present research is a great step in the design and study of videos at the university level of Financial Mathematics. This research is motivated by the call for more extensive research into the effectiveness of video tutorials [33], [35], or [39]. To the best of our knowledge, previous studies that analyze the effectiveness of videos employing PLS-SEM methodology are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Technological progress is a reality in the higher education field, not least since the COVID-19 pandemic. Most universities moved to online learning environments to replace face-to-face classes [33]. The concept of e-learning includes the use of new technologies and the Internet to improve the quality of learning by facilitating access to resources as well as remote exchanges and collaboration [34].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation